2009
DOI: 10.1007/s10549-009-0444-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-carotene, vitamin C and E intake and breast cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: So far, studies on dietary antioxidant intake, including beta-carotene, vitamin C and vitamin E, and breast cancer risk are inconclusive. Thus, we addressed this question in the European Prospective Investigation into Cancer and Nutrition. During a median follow-up time of 8.8 years, 7,502 primary invasive breast cancer cases were identified. Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). All analyses were run stratified by menopausal status at recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 42 publications
2
39
1
2
Order By: Relevance
“…After screening, 51 studies entered the metaanalysis. As shown in Supplemental Table 1, there were 36 case-control studies, including 23 hospital-based casecontrol studies [10-12, 14, 16, 24, 26, 28, 29, 31, 42-54] and 13 population-based case-control studies [17-20, 22, 23, 25, 30, 32, 55-58], 2 nested case-control studies [13,59], 1 case-cohort study [60], 9 cohort studies [8,9,15,21,27,[61][62][63][64], and 3 RCTs [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 51 studies entered the metaanalysis. As shown in Supplemental Table 1, there were 36 case-control studies, including 23 hospital-based casecontrol studies [10-12, 14, 16, 24, 26, 28, 29, 31, 42-54] and 13 population-based case-control studies [17-20, 22, 23, 25, 30, 32, 55-58], 2 nested case-control studies [13,59], 1 case-cohort study [60], 9 cohort studies [8,9,15,21,27,[61][62][63][64], and 3 RCTs [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…In 3 studies, the ORs were analyzed in pre-and postmenopausal women, respectively [8,23,27]. In 3 other studies [55,59,64], the ORs for dietary vitamin C (or total vitamin C) and vitamin C supplements were analyzed separately, so we considered them to be 12 independent comparisons.…”
Section: Vitamin Cmentioning
confidence: 99%
“…Besides genetic variants, several other factors may also affect the balance of oxidants and antioxidants directly or indirectly. For example, endogenous and exogenous exposures, such as intake of selenium, fruits, and vegetables, are involved in the maintenance of this balance, and have been proved to be associated with low cancer risk [25][26][27][28][29]. Alcohol consumption and smoking are two important environmental factors which are believed to participate in breast cancer development [30], and studies have showed that they may influence the GPX1 activity [4].…”
Section: Discussionmentioning
confidence: 99%
“…No meta-analysis about the associations between a-carotene, b-cryptoxanthin, lutein/?zeaxanthin, and lycopene and breast cancer has been reported. Since the first two metaanalyses were published, 20 inconsistent observational studies with large samples have been published [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Meanwhile, among the carotenoids, which one play a greater role in reducing breast cancer risk remains unclear.…”
Section: Introductionmentioning
confidence: 99%